Algorithm analysis termohramy airfield surface coating - Дмитрієв, М.М.; Папченко, О.М.; Деркачов, О.Б.; Рутковська, І.А. (Proceedings of National Aviation University, 2008)
There are worked out scientific-methodical aspects of detection of airfield covering’s latent damages by non-destructive heat method. The method is based on mathematic model of the heat field of covering, depending from seasons and time of the day. There are no problems for its automation. The real example of analysis is given.